Influence of pre-exercise soybean-based beverage on biochemical and physiological responses in healthy men / Albert Tan Yi Wey - Albert Tan , Yi Wey (2019)
Whey protein, when added with carbohydrate (CHO) beverage, has been shown to lower the postprandial blood glucose and insulin, which may help to attenuate postprandial reactive oxygen species (ROS) and inflammation. Whey added CHO beverage consumption also has shown to reduce oxidative stress, muscle inflammation and damage as well as improved exercise performance. Soybean contains isoflavones which may provide the possibility of having similar positive effects or better than whey protein when added with CHO beverage. The first study aimed to investigate the effects of soybean added CHO beverage consumption in comparison to whey added CHO beverage on postprandial glycemic, insulinemic and ROS in healthy men. Eight males [age 20 (1.2) years, body weight 59.2 (6.2) kg] consumed 500 ml of CHO added with soybean (SOY+CHO), CHO added with whey protein (WHEY+CHO) and CHO alone (Control) after an overnight fast, in a randomized counterbalanced order, separated by a one-week period. Venous blood samples were collected after an overnight fast (baseline) and at 30, 60, 90 and 120 min after consumption of the beverage. The area under the insulin curve was lower in SOY+CHO compared to WHEY+CHO. Similarly, SOY+CHO tended to have a lower postprandial ROS response than WHEY+CHO. However, no significant difference was observed between all beverages. The soybean-based beverage may yield lower effect on postprandial ROS suggesting lower oxidative stress due to lower insulinemic responses, compared to whey protein when co-ingested with CHO. The second study was to investigate the effects of pre-exercise SOY+CHO as compared with WHEY+CHO consumption on antioxidant activity, oxidative stress, muscle damage and inflammation, total cycling workload and fatigue perception post cycling at 85% VO2peak and subsequent cycling in physically active males. In randomized counterbalanced order, seven physically active males [age 20 (0.9) years, peak oxygen consumption 49.3 (0.3) L/min] performed three cycling exercise at 85%VO2peak after the consumption of 500 ml SOY+CHO, WHEY+CHO and CHO (Day 1) and repeated the same experimental protocol with the same trial on the next day (Day 2). On each trial, blood samples were collected after an overnight fast and at pre-exercise, post exercise and 1-hour post exercise after consumption of the beverage for the analysis of ferric reduced antioxidant power (FRAP), glutathione (GSH), oxidized glutathione (GSSG), glutathione ratio (GSH/GSSG), interleukin-6 (IL-6) and creatine kinase (CK). The rate of perceived exertion (RPE) and total workload (kilopond) were recorded at post exercise. There was no significant main effect between SOY+CHO and WHEY+CHO for FRAP, IL-6, GSH, GSSG, glutathione ratio, CK, total workload and RPE in Day 1 and subsequent Day 2. The differences between Day 1 and Day 2 at post cycling and 1 hour post exercise were not significantly different between SOY+CHO and WHEY+CHO for all the parameters. Compared to the CHO, no significant difference in all parameters was observed. These preliminary results suggest that soybean-based beverage may have a similar impact on antioxidant activity, oxidative stress, muscle inflammation, muscle damage, perceived fatigue and exercise performance, compared to whey protein when co-ingested with CHO.